Reflections on public property from an analysis of the evolution and recent trends in the commons - Girardi, Maria Chiara (Diritto Pubblico Europeo - Rassegna online, 2023)
The paper analyses the evolution and recent trends of common goods, in order to reflect on the advisability of amending the codified regulation of public goods, in order to enhance their social function. The legal recognition of commons requires, however, in advance, a rethinking of the State model, in order to make the concept of social function prevail over that of belonging. From this perspective, the Andean Constitutions represent the first example of the constitutionalisation of common goods, but above all an important example of the valorisation of citizens’ interests in the use of goods such as natural resources. Beyond the different doctrinal positions in the field, on whether it is appropriate to introduce the legal category of common goods, these studies return the widespread conviction of the need to modify the discipline of public goods provided for in the Civil Code, in order to valorise the social function of these goods, in the interest of citizens and in line with the welfare State